2017
DOI: 10.2500/aap.2017.38.4029
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of chronic spontaneous urticaria in childhood is associated with the urticaria activity score

Abstract: The etiology of CSU in children was mostly idiopathic despite detailed investigation. In childhood, the natural course of CSU was favorable, and nearly half of the patients recovered after 5 years of disease duration. A high UAS7 at admission seemed to be a significant risk factor for the persistence of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
51
1
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 0 publications
9
51
1
10
Order By: Relevance
“…Isolated wheals appear in 78.4% of cases, angioedema in 6.65%, while both symptoms are observed in 15% of cases . In children, accompanying angioedema was reported in 48.2% cases …”
Section: Histological and Clinical Characterizationmentioning
confidence: 96%
“…Isolated wheals appear in 78.4% of cases, angioedema in 6.65%, while both symptoms are observed in 15% of cases . In children, accompanying angioedema was reported in 48.2% cases …”
Section: Histological and Clinical Characterizationmentioning
confidence: 96%
“…Хроническая кра-пивница выраженно снижает качество жизни ребенка, ухудшает ночной сон, влияет на успеваемость в школе, в том числе из-за пропусков занятий в связи с частыми обострениями [5,6]. Заболевание оказывает отрица-тельное влияние на качество жизни не только самого ребенка, но и его семьи и окружения [1,7].…”
Section: Introductionunclassified
“…However, we believe this is unlikely given the severity of our patient’s urticaria and need for combination therapy, which are risk factors for persistent disease. 5,10 Furthermore, a recent study of children with CSU observed remission in only 10.6% and 44.5% of patients at 1 and 5 years, respectively. 5 Although further study is needed, this case demonstrates that hydroxychloroquine can be a safe and potentially effective therapeutic option for antihistamine-refractory CSU in children, allowing for concomitant discontinuation of steroids.…”
mentioning
confidence: 97%
“…4 Childhood CSU is sometimes associated with infections, atopy, autoimmunity and physical urticarias, but most cases are idiopathic. 5 Although large clinical studies are lacking, many children with recurrent urticaria appear to respond favorably to antihistamines. 6 However, the optimal management of antihistamine-refractory CSU in children is unknown.…”
mentioning
confidence: 99%